Identification of Digital Sharia Banking Development as a Catalyst for Sharia Financial Inclusion in Indonesia - Tamami, Muhammad In’amullah; Anggraini, Ika Khusnia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The banking industry has undergone a technological revolution, leading to the emergence of digital banks that offer technology-based services accessible through smart devices. This has had a positive impact on financial inclusion by providing easier access to banking services to a wider community. However, the growth of Islamic banking has not shown the same progress due to the limited development of Islamic digital banks. To address this issue, a qualitative study was conducted to identify opportunities for product development in Islamic digital banks, aiming to promote Islamic financial inclusion. Data from interviews, reports, fatwas, and articles were analyzed using data triangulation methods. The study revealed innovative approaches to improving Islamic digital banking, particularly in products and services that serve community transactions. These identified innovations offer promising steps to increase the level of Islamic inclusion.